Accuracy of liquid based versus conventional cytology: overall results of new technologies for cervical cancer screening: randomised controlled trial. Issue 7609 (21st May 2007) - Ronco, Guglielmo; Cuzick, Jack; Pierotti, Paola; Cariaggi, Maria Paola; Palma, Paolo Dalla; Naldoni, Carlo; Ghiringhello, Bruno; Giorgi-Rossi, Paolo; Minucci, Daria; Parisio, Franca; Pojer, Ada; Schiboni, Maria Luisa; et al.
Abstract : Objective To compare the accuracy of conventional cytology with liquid based cytology for primary screening of cervical cancer. Design Randomised controlled trial. Setting Nine screening programmes in Italy. Participants Women aged 25-60 attending for a new screening round: 22 466 were assigned to the conventional arm and 22 708 were assigned to the experimental arm. Interventions Conventional cytology compared with liquid based cytology and testing for human papillomavirus. Main outcome measure Relative sensitivity for cervical intraepithelial neoplasia of grade 2 or more at blindly reviewed histology, with atypical cells of undetermined significance or more severe cytology considered a positive result. Results In an intention to screen analysis liquid based cytology showed no significant increase in sensitivity for cervical intraepithelial neoplasia of grade 2 or more (relative sensitivity 1.17, 95% confidence interval 0.87 to 1.56) whereas the positive predictive value was reduced (relative positive predictive value v conventional cytology 0.58, 0.44 to 0.77). Liquid based cytology detected more lesions of grade 1 or more (relative sensitivity 1.68, 1.40 to 2.02), with a larger increase among women aged 25-34 (P for heterogeneity 0.0006), but did not detect more lesions of grade 3 or more (relative sensitivity 0.84, 0.56 to 1.25). Results were similar when only low grade intraepithelial lesions or more severe cytology were considered a positive result. No evidence was found of heterogeneity between centres or of improvement with increasing time from start of the study. The relative frequency of women with at least one unsatisfactory result was lower with liquid based cytology (0.62, 0.56 to 0.69). Conclusion Liquid based cytology showed no statistically significant difference in sensitivity to conventional cytology for detection of cervical intraepithelial neoplasia of grade 2 or more. More positive results were found, however, leading to a lower positive predictive value. A large reduction in unsatisfactory smears was evident. Trial registration Current Controlled Trials ISRCTN81678807 .